Filsafat dan Perubahan Perilaku Keagamaan Santri di Pondok Pesantren Mahasiswa Muthahhari Yogyakarta - Agung, Ahmad; Mustika Sari, Ramadhanita (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
This paper examines educational institutions based on boarding schools and boarding schools, whose main material is philosophy. This educational institution is oriented towards critical and objective religious awareness. The actualization of this awareness is in the form of changes in religious behavior in the students themselves. This is urgent to study because as time goes by, secularism also influences the behavior of students getting further away from their religious values. This is caused by low religious literacy in Islamic boarding schools. As a result, a generation of semi-secular intellectuals grows, the knowledge they possess does not lead them to behave religiously. They have religious identity but their behavior is far from religious values. The problem is then formulated into the question how does social construction implement changes in the religious behavior of students? The object of this research is the Motahhari Islamic Boarding School (PPM), Yogyakarta. The Islamic boarding school is a philosophy boarding school in Yogyakarta. This research is a field research. The theory used to analyze and answer research problems is the social construction theory of Peter L Berger and Thoman Luckman. Data collected by observation techniques, interviews and documentation. The results of this study indicate that changes in religious behavior that occur in students at the Motahhari Yogyakarta Islamic Boarding School (PPM) are formed through three stages, namely externalization, objectivation and internalization